A method for the aerodynamic design of dry powder inhalers - Ertunc, Özgür; Köksoy, Cagatay; Wachtel, Herbert; Delgado, Antonio (International Journal of Pharmaceutics, 2011)
An inhaler design methodology was developed and then used to design a new dry powder inhaler (DPI) which aimed to fulfill two main performance requirements. The first requirement was that the patient should be able to completely empty the dry powder from the blister in which it is stored by inspiratory effort alone. The second requirement was that the flow resistance of the inhaler should be geared to optimum patient comfort. The emptying of a blister is a two-phase flow problem, whilst the adjustment of the flow resistance is an aerodynamic design problem. The core of the method comprised visualization of fluid and particle flow in upscaled prototypes operated in water. The prototypes and particles were upscaled so that dynamic similarity conditions were approximated as closely as possible. The initial step in the design method was to characterize different blister prototypes by measurements of their flow resistance and particle emptying performance. The blisters were then compared with regard to their aerodynamic performance and their ease of production. Following selection of candidate blisters, the other components such as needle, bypass and mouthpiece were dimensioned on the basis of node-loop operations and validation experiments. The final shape of the inhaler was achieved by experimental iteration. © 2011 Elsevier B.V. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.ametho
Keywords: Design; DPI; Dry powder; Flow visualization; Fluid mechanics; Inhaler